Erosion von Verfassungsvoraussetzungen : Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Erlangen vom 1. bis 4. Oktober 2008. - Sacksofsky, Ute (De Gruyter, 2009)
This volume presents the reports and discussions held at the conference of the "Association of German Constitutional Teachers" in Erlangen from October, 1st to October, 4th, 2008.
Keywords: Constitutional history -- Germany -- Congresses.; Constitutional law -- Germany -- Congresses.; Democracy -- Germany -- Congresses.; Constitutional history.; Constitutional law.; Democracy.; Germany.; Electronic books.; Conference papers and proceedings.